2020
DOI: 10.1002/jts.22591
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder Following Myocardial Infarction: A Systematic Review

Abstract: The objective of the present review is to provide an overview of existing research that has reported on the association between posttraumatic stress disorder (PTSD) and ischemic heart disease. Specific focus is given to the incidence of PTSD following myocardial infarction (MI). A systematic review using Preferred Reporting Items for Systematic reviews and Meta‐Analysis (PRISMA) guidelines was performed by searching four bibliographic databases: PubMed, PsychINFO, ScienceDirect, and ProQuest Dissertations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…The affected person would often be unaware of what is happening, experience excruciating chest pain and shortness of breath, become anxious, and fear death ( 2 , 3 ). Such an experience may indeed be considered a traumatic event, and symptoms of PTSD may subsequently develop ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The affected person would often be unaware of what is happening, experience excruciating chest pain and shortness of breath, become anxious, and fear death ( 2 , 3 ). Such an experience may indeed be considered a traumatic event, and symptoms of PTSD may subsequently develop ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…ASD was found to be prevalent in 18% of patients with acute coronary syndromes (ACS), such as AMI 4 . ASD is associated with impaired quality of life and adverse cardiovascular consequences after ACS 5 , 6 . Age is a predictor of ASD, and Ghada et al found that the risk of ASD in young persons following stressful events is greater than in the elderly 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of ASD has been reported in 18% of patients with acute coronary syndromes (ACS), such as AMI 4 . ASD is associated with impaired quality of life and adverse cardiovascular consequences after ACS 5,6 . Age is a predictor of ASD, and Ghada et al found that the risk of ASD in young people after traumatic events is more signi cant than that in the elderly 7 .…”
Section: Introductionmentioning
confidence: 99%